(untitled) (Bangladesh Medical Journal Khulna, 2017)
Alkaptonuria is a rare metabolic autosomal recessive disorder. It occurs due to lack of an enzyme that results in deposition of homogentisic acid in various tissues. A male patient of 45 years presented with back pain for 20 years and multiple joint pain for 10 years. Patient has multiple nodules in both pinnae and pigmentation in both sclerae. His urine turns black upon standing. These findings are compatible with the diagnosis of Alkaptonuria. Bang Med J (Khulna) 2016; 49 : 37-39